Making museum research more visible: Open Access in the GLAM sector - Emily Rees Koerner; Lydia Ackrell (Science Museum Group Journal)
Open Access paradigms have changed how academic scholarship is published and disseminated, creating a new model for how research is shared. But how do these paradigms map onto museum research? This question is particularly pertinent when larger numbers of funded research projects include, or are led by, museums. This article considers some of the affordances and challenges of using Open Access principles and technologies to make visible the multifaceted modes of research that take place in a museum setting. Using the Science Museum Group as a case study, it focuses on how repositories offer one means to make research conducted in museums more accessible, while also broadening definitions of what a research output is. With the focus hitherto more on images and collection items, here we expand into the realm of exhibition and gallery outputs – the content which museums produce to narrate their collections’ stories and engage audiences. Many of these outputs may have been designed to have an ephemeral, physical lifespan, but through platforms such as repositories they can gain a digital afterlife, serving a new purpose as learning resources, research data, or indeed a record of curatorial and museological practice. The article ultimately argues that Open Access principles can aid museums (and the wider GLAM sector) in their mission to be transparent organisations for wide-ranging audiences.